Periodontal Analysis of Teeth with Biological Space Invasion submitted to Root Extrusion and Prosthetic Rehabilitation: Literature Review - Morel, Laura Lourenço; Silva, Lucas Jardim da; Gomes, Giovane; Martos, Josué (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Aim: The purpose of this literature review was to identify whether root traction may maintain the periodontal health of teeth with invasion of supracrestal tissue attachment and prosthetically rehabilitated. Materials and Methods: A literature review was conducted, in which the periodontal effects of root traction provided on the ability to maintain teeth with invasion of supracrestal tissue attachment and prosthetically rehabilitated were searched in the electronic databases Scopus, PubMed, Web of Science, EMBASE, Scielo and Cochrane using the Mesh descriptors "orthodontic extrusions", "forced eruption" and "crown lengthening". The inclusion criteria considered studies published in English or Spanish that presented the relationship between root traction and the effect on periodontal health in prosthetically rehabilitated teeth. After collection of articles, they were evaluated by three reviewers, who selected the studies according to their relevance according to criteria as type of study, root traction present, rehabilitation with single fixed prosthesis and period of clinical follow-up. Results: A total of 644 references were identified and after exclusion according to eligibility criteria, 33 papers covered all parameters adopted and were included in the qualitative analysis. Satisfactory prosthetic rehabilitation, associated with periodontal health after root traction, could be observed in all studies, notably with variation only in the follow-up time observed up to the first six months, 1, 2, 3 and up to 4 years. Conclusions: Root traction is a conservative and effective tool in the maintenance of periodontal health in teeth with invasion of supracrestal tissue attachment and prosthetically rehabilitated.